2011
DOI: 10.1287/orsc.1100.0597
|View full text |Cite
|
Sign up to set email alerts
|

Status Inconsistency and Product Valuation in the California Wine Market

Abstract: This study develops a theoretical model on the role of multidimensional status and status inconsistency in market evaluation processes. A product or an organization may acquire multiple status indicators in association with a multitude of market institutions. We argue that when status indicators are consistently positive, each exerts a greater positive effect on the valuation of a product or an organization; conversely, inconsistency among multiple indicators undermines the status claim. We test this theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 43 publications
0
49
2
Order By: Relevance
“…While there has been considerable research interest in valuation processes and outcomes (Callon and Muniesa 2005;Hsu, Roberts, and Swaminathan 2012;Espeland and Sauder 2007;Rao, Monin and Durand 2003;Waguespack and Sorenson 2011;Zhao and Zhou 2011), we currently know little about what happens when valuations move online. We addressed this gap by conducting an empirical study in the travel sector, focusing specifically on two primary research questions: how do practices of valuation change when they are produced online by consumers?, and what outcomes do such online valuations generate for the organizations being evaluated?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been considerable research interest in valuation processes and outcomes (Callon and Muniesa 2005;Hsu, Roberts, and Swaminathan 2012;Espeland and Sauder 2007;Rao, Monin and Durand 2003;Waguespack and Sorenson 2011;Zhao and Zhou 2011), we currently know little about what happens when valuations move online. We addressed this gap by conducting an empirical study in the travel sector, focusing specifically on two primary research questions: how do practices of valuation change when they are produced online by consumers?, and what outcomes do such online valuations generate for the organizations being evaluated?…”
Section: Introductionmentioning
confidence: 99%
“…The organizational implications of such heightened scrutiny have been considerable (Espeland and Sauder 2007;Martins 2005) -increasing the visibility and accountability of processes and outcomes, while intensifying strategic and operational concerns with criteria, metrics, and assessment. Such implications are likely to become even more influential as evaluations move online, becoming widespread, consumer-based, globally dispersed, and widely accessible.In the move to online reviewing, established forms of valuation are challenged, as the rise of the Internet and social media in particular blurs traditional distinctions between production and consumption.Valuations -which have traditionally been produced by a small number of recognized experts, critics, media, and authorities using formal, standardized and often institutionalized criteria grounded in professional knowledge and industry experience -are now also (and increasingly) being produced online by large numbers of anonymous and distributed consumers using informal, variable, and individual criteria grounded in personal opinions and experiences.While there has been considerable research interest in valuation processes and outcomes (Callon and Muniesa 2005;Hsu, Roberts, and Swaminathan 2012;Espeland and Sauder 2007;Rao, Monin and Durand 2003;Waguespack and Sorenson 2011;Zhao and Zhou 2011), we currently know little about what happens when valuations move online. We addressed this gap by conducting an empirical study in the travel sector, focusing specifically on two primary research questions: how do practices of valuation change when they are produced online by consumers?, and what outcomes do such online valuations generate for the organizations being evaluated?…”
mentioning
confidence: 99%
“…The importance of aligning expectations in the evaluator's mind may be one reason that other scholars have found that status has its greatest effect on economic performance advantages when there is consistency among multiple status signals (Zhao and Zhou 2011). Both status and reputation influence perceptions because they shape performance expectations.…”
Section: Resultsmentioning
confidence: 99%
“…Second, prior research has theorized that existing ratings may provide a positive or a negative anchor for future ratings (Li & Hitt, 2008;Moe & Trusov, 2011;Muchnik et al, 2013;Schlosser, 2005;Waguespack & Sorenson, 2011;Zhao & Zhou, 2011). These anchors create a Matthew effect whereby the rich get richer (positive anchors) and the poor get poorer (negative anchors) (Merton, 1968).…”
Section: Online Ratingsmentioning
confidence: 99%
“…Both the online and the offline ratings' literature have consistently found that existing ratings provide a positive or a negative anchor for future ratings, which leads to a Matthew effect for content contributors (Li & Hitt, 2008;Moe & Trusov, 2011;Muchnik et al, 2013;Schlosser, 2005;Waguespack & Sorenson, 2011;Zhao & Zhou, 2011). However, I propose that the power distance of the rater's national culture will moderate this effect because individuals socialized in high power distance cultures have a greater tendency to act deferentially to those in high-status positions, whereas individuals socialized in low power distance cultures generally have less respect for those in high-status positions (Erez & Gati, 2004;Hofstede & Bond, 1988;Triandis, 2000).…”
Section: Interaction Of Power Distance and Contributor Matthew Effectmentioning
confidence: 99%